Powdery Mildew of Echinacea purpurea Caused by Podosphaera xanthii in China - Zhang, Fuhai; Zhang, Shaohui; Wu, Yanpan; Liu, Juncong; Zhao, Sujing; Qiu, Zongbo; Zhu 朱, Mo 墨 (Plant disease, 2025)
Echinacea purpurea (Eastern Purple Coneflower) is a perennial herbaceous plant belonging to the Asteraceae. It originated from North America and is cultivated all over the world. Extracts of E. purpurea are widely used for the treatments of colds and sore throats (Jiao et al. 2020). In October 2024, powdery mildew-like signs and symptoms were observed on leaves of E. purpurea plants (n=100) cultivated in a garden (20 m2) in Xinxiang city, Henan Province, China (35.32° N, 113.92° E). A specimen (PX-ZM20241024) was stored in Xinxiang Key Laboratory of Plant Stress Biology. The infected leaves were covered with white and thin masses and showed senescence symptoms. More than 80% of plants (n=100) exhibited these signs and symptoms. White colonies were on both sides surfaces of the leaves, covering about 80% of the leaf area. The slightly curved or straight Conidia chain (n = 50) were 70 to 156 × 8 to 12 μm in size and consisted of foot cells, shorter cells, and conidia. Foot cells were straight, 30 to 60 μm long. Conidia were ellipsoid to oval, 20 to 35 × 12 to 17 μm (n = 50), with a length/width ratio of 1.8 to 2.2, containing fibrosin bodies. These morphological characteristics were similar to Podosphaera xanthii (Braun and Cook 2012). Following a previously reported method (Zhu et al. 2022), the internal transcribed spacer (ITS) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) regions of a selected specimen of the fungus were amplified and sequenced with primers ITS1/ITS4 (White et al. 1990) and GAPDH1/GAPDH3R (Bradshaw et al. 2022). The resulting sequences were deposited in GenBank (Accession No. PQ508348 and PQ734986). BLASTn analysis indicated that the ITS and GAPDH sequences had 99.82 % (564/565 bp) and 100% (238/238 bp) identity with reported P. xanthii (MW300956 and ON075660) on Xanthium strumarium and Cucurbita moschata, respectively (Zhu et al. 2024; Bradshaw et al. 2022). By phylogenetic analysis, the isolated fungus clustered with previously reported P. xanthii (Zhu et al. 2024; Bradshaw et al. 2022). Therefore, the morphology and phylogenetic analysis indicated that the pathogen was P. xanthii. To complete Koch's postulates, mature leaves of three healthy E. purpurea (30 cm high) were inoculated with fungal conidia by gently pressing surfaces of infested leaves onto leaves of healthy plants. Three untreated plants served as controls. Both the control and inoculated plants were separately placed in greenhouses (humidity, 60%; light/dark, 16 h/8 h; temperature, 18°C). 10 to 12 days post inoculation, the leaves of the inoculated plants exhibited signs of powdery mildew, whereas the control group remained unaffected. The experiments were repeated three times and the same results were obtained. Therefore, the pathogenicity of this fungal pathogen was confirmed. Previously, P. xanthii was reported on E. purpurea in Korea (Choi et al. 2020). To the best of our knowledge, this is the first report of P. xanthii on E. purpurea in China. The sudden presence of powdery mildew caused by P. xanthii may adversely affect plant health and thus reduce the medicinal value of E. purpurea. Therefore, the identification and confirmation of P. xanthii infecting E. purpurea enhances our comprehension of hosts of this pathogen and provides fundamental information for forthcoming disease control studies.